Correction: Making the move towards modernized greener separations: introduction of the analytical method greenness score (AMGS) calculator. Issue 23 (19th November 2020) - Hicks, Michael B.; Farrell, William; Aurigemma, Christine; Lehmann, Laurent; Weisel, Lauren; Nadeau, Kelly; Lee, Heewon; Moraff, Carol; Wong, Mengling; Huang, Yun; Ferguson, Paul
Abstract : Correction for 'Making the move towards modernized greener separations: introduction of the analytical method greenness score (AMGS) calculator' by Michael B. Hicks et al., Green Chem., 2019, 21, 1816–1826, DOI: ; 10.1039/C8GC03875A .